Update on omalizumab in allergen immunotherapy. Issue 6 (December 2021) - Dantzer, Jennifer A.; Wood, Robert A.
Abstract : Purpose of review: To review the most relevant studies in the advancing field of omalizumab in allergen immunotherapy. Recent findings: Omalizumab has been used in combination with inhalant, venom, and food allergen immunotherapy. These studies suggest that omalizumab can decrease the time required to reach maintenance dosing and adverse events. However, severe adverse events do still occur. Limited long-term data suggests that there is a risk for increased reactivity after stopping omalizumab. Summary: Omalizumab in conjunction with immunotherapy has shown promising results for the treatment of allergic rhinitis, venom hypersensitivity, and food allergy, especially in the reduction of adverse events. Larger randomized, placebo-controlled trials are needed to better understand optimal dosing and duration, cost-–benefit analysis, ideal patients, and long-term benefits. This combination therapy has the potential to improve treatment, particularly for high–risk patients.